2021
DOI: 10.1108/ies-07-2020-0025
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting Sharīʿah audit quality in Islamic banking institutions of Pakistan: a theoretical framework

Abstract: PurposeThe objective of this study is to present a theoretical framework, which helps ascertain the meanings of the Sharīʿah audit quality and identify the factors that affect it.Design/methodology/approachThe current literature of conventional and Islamic finance on audit quality is critically reviewed to propose the theoretical framework for the quality of Sharīʿah audit.FindingsThe paper suggests that for a better Sharīʿah compliance at Islamic banking institutions (IBIs), the role of audit practitioners is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…The competence of practitioners becomes one of the essential factors that affect the quality of sharia audits. Different contracts, financial arrangements, and transactions require unique competencies on the part of the auditor, i.e., tightening sharia law in addition to old assurance skills and techniques [8]. Rifai's research also found that auditor organizational commitment and integrity positively affect fraud prevention [9].…”
Section: Nomentioning
confidence: 99%
See 1 more Smart Citation
“…The competence of practitioners becomes one of the essential factors that affect the quality of sharia audits. Different contracts, financial arrangements, and transactions require unique competencies on the part of the auditor, i.e., tightening sharia law in addition to old assurance skills and techniques [8]. Rifai's research also found that auditor organizational commitment and integrity positively affect fraud prevention [9].…”
Section: Nomentioning
confidence: 99%
“…The influence of audit quality, on the other hand, affects the competence of practitioners. Unique competencies on the part of the auditor needed to tighten sharia law in addition to old assurance skills and techniques [8]. In addition, the integrity of the auditor and the organization's commitment positively affect fraud preventionssss [9].…”
Section: Introductionmentioning
confidence: 99%
“…Shahar et al (2018) which discusses sharia audit for Islamic financial institutions. Rashid & Ghazi (2021) present a theoretical framework, which helps ascertain the meaning of Sharia audit quality and identify the factors that influence it. And, Shafii et al (2010) discuss the development of a Shariah compliance audit framework and a Shariah audit program to manage Shariah non-compliance audit risk in Islamic financial institutions.…”
Section: Introductionmentioning
confidence: 99%
“…explain the conceptual framework for the effectiveness of Islamic internal audit factors in Islamic banks.Wan Shahar et al (2018) which discusses sharia auditing for Islamic financial institutions. AbdulRahman (2010) explains the needs and challenges of Sharia Audit for Islamic Financial Services Rashid & Ghazi (2021). present a theoretical framework, which helps ascertain the meaning of Shariah audit quality and identify the factors that influence it.…”
mentioning
confidence: 99%